Impact of dietary carbohydrate restriction on the pathobiology of Hepatocellular Carcinoma: The gut-liver axis and beyond. (March 2023) - Cramer, Thorsten
Abstract: Despite decades of fiercely competitive research and colossal financial investments, the majority of patients with advanced solid cancers cannot be treated with curative intent. To improve this situation, conceptually novel treatment approaches are urgently needed. Cancer is increasingly appreciated as a systemic disease and numerous organismal factors are functionally linked to neoplastic growth, e.g. systemic metabolic dysregulation, chronic inflammation, intestinal dysbiosis and disrupted circadian rhythms. It is tempting to hypothesize that interventions targeting these processes could be of significant account for cancer patients. One important driver of tumor-supporting systemic derangements is inordinate consumption of simple and highly processed carbohydrates. This dietary pattern is causally linked to hyperinsulinemia, insulin resistance, chronic inflammation and intestinal dysbiosis, begging the pertinent question whether the adoption of dietary carbohydrate restriction can be beneficial for patients with cancer. This review summarizes the published data on the role of dietary carbohydrate restriction in the pathogenesis of Hepatocellular Carcinoma (HCC), the most frequent type of primary liver cancer. In addition to outlining the functional interplay between diet, the intestinal microbiome and immunity, the review underscores the importance of bile acids as interconnectors between the intestinal microbiota and immune cells.